The Implementation of Numbered Heads Together (NHT) Technique in Teaching Speaking Skill at IX Grade of SMPN 7 Bukitinggi - Humairoh, Suci; Roza, Veni; Reflinda, Reflinda; Melani, Melyann (Pusdikra Publishing, 2024)
This research was conducted based on problems found by researchers in the learning process about speaking skills using the Numbered Heads Together (NHT) technique. Numbered Heads Together (NHT) is cooperative learning that focuses on influencing communication to help students face a problem by discussing their best ideas about the problem. NHT is a technique that teachers have implemented in the classroom to teach students speaking skills. Teachers must be clever in choosing learning methods or techniques that will be used in teaching because learning techniques are fundamental forms or concrete ways of implementing learning during the learning process to achieve learning goals. This research aims to determine how teachers implement the Numbered Heads Together (NHT) technique in teaching students' speaking skills, whether it is in accordance with theory or not. The method used in this research is descriptive qualitative research, which aims to describe how teachers implement the Numbered Heads Together (NHT) technique in teaching speaking skills. Then, the instrument used in this research was an observation sheet. The teacher teaches Present Continuous 'What are you doing?' and asks students to sit in small groups using NHT to discuss assignments given by the teacher. The results of this research show that teachers do not fully implement the steps of the Numbered Heads Together (NHT) technique in teaching speaking skills because the teacher has limited the time. Keywords: Implementation, Numbered Heads Together, Speaking skill.